Comparative study of antiretroviral drug regimens and drug–drug interactions between younger and older HIV-infected patients at a tertiary care teaching hospital in South Korea - Park MS; Yang YM; Kim JS; Choi EJ (Dove Medical Press, 2018)
Mi Seon Park,1,* Young-Mo Yang,2,* Ju-Sin Kim,1 Eun Joo Choi2 1Department of Pharmacy, Chonbuk National University Hospital, Jeonju, South Korea; 2Department of Pharmacy, College of Pharmacy, Chosun University, Gwangju, South Korea *These authors contributed equally to this work Background: With the advent of combination antiretroviral therapy (ART), people living with HIV have lived to older age. So they have experienced age-related illnesses and have taken non-antiretroviral (ARV) medications to manage these illnesses. The aims of this study were to investigate the use patterns of ARV agents in HIV-positive patients by age and to evaluate potential or contraindicated drug–drug interactions (DDIs) between ARV and non-ARV. Methods: This study was retrospectively conducted with HIV-infected patients receiving ART medications between October 2011 and September 2017 at Chonbuk National University Hospital in South Korea. Data were collected by reviewing patients’ electronic medical charts. Results: Among 207 patients diagnosed with HIV infection, 183 (86.9% males; 104 aged <50 years and 79 aged ≥50 years) were selected based on inclusion criteria. In 2017, the most frequently prescribed ART regimen was nucleoside reverse transcriptase inhibitors (NRTIs)/integrase strand transfer inhibitors (INSTIs; total, 66.3%; <50 years, 36.3%; ≥50 years, 30.0%) followed by NRTIs/protease inhibitors (PIs; total, 23.8%; <50 years, 15.0%; ≥50 years, 8.8%). In 2017, the most frequently prescribed NRTI combination was abacavir/lamivudine (total, 34.4%; <50 years, 20.6%; ≥50 years, 13.8%) followed by tenofovir alafenamide/emtricitabine (FTC; total, 31.3%; <50 years, 16.3%; ≥50 years, 15.0%) and tenofovir disoproxil fumarate/FTC (total, 28.1%; <50 years, 16.9%; ≥50 years, 11.3%). In 2017, elvitegravir (EVG)/cobicistat (COBI; total, 57.1%; <50 years, 30.4%; ≥50 years, 26.8%) was most frequently prescribed followed by dolutegravir (total, 32.1%; <50 years, 19.6%; ≥50 years, 12.5%). Potential or contraindicated DDIs between boosted PIs with ritonavir or EVG/COBI and coprescribed drugs occurred most frequently. Conclusion: Currently, NRTIs/INSTIs is the most frequently prescribed ARV combination. Abacavir/lamivudine, tenofovir alafenamide/FTC, and tenofovir disoproxil fumarate/FTC are the most used NRTIs, and EVG/COBI followed by dolutegravir is the most prescribed INSTIs. Potential or contraindicated DDIs occur mainly between boosted PIs or EVG/COBI and non-ARV medications. Keywords: human immunodeficiency virus, highly active antiretroviral therapy, drug utilization, drug interactions, Korea, elderly patients